Comparison of Whole Blood and Plasma for Dengue Virus RNA Detectionby Reverse Transcriptase - PCR - Palmares, Aaron Jan S; Baclig, Michael O. (Asian Journal of Biological and Life Sciences, 2018)
Aiming at the improvement of the molecular diagnosis of dengue infection, whole blood and plasma samples from 31 suspected dengue patients admitted at San Lazaro Hospital (Manila, Philippines) were examined using dengue RT-PCR. Using TRIzol® for whole blood and TRIzol® LS for its corresponding plasma in the RNA extraction phase, 26 (84%) whole blood samples were positive while its only 15 (48%) for its corresponding plasma (P=0.001). In contrast to screening with SD BIOLINE® dengue NS1 antigen test of which 24 (77%) was positive, plasma RT-PCR have significantly lower results (P=0.035) while there is no significant difference for whole blood RT-PCR (P=0.727). In contrast to SD BIOLINE® dengue antibody test (IgM and/or IgG) of which 13 (42%) were positive, whole blood RT-PCR obtained a significantly higher result (P=0.004) while there is no significant difference with plasma RT-PCR (P=0.832). These results indicate that the better specimen for RNA extraction for dengue diagnosis by RT- PCR is the whole blood. Aside from rapid detection and quantification of viral load, increasing the success rate of RNA extraction can be useful for molecular epidemiological studies involving classification of dengue into different serotypes and genotypes, and characterization of dengue strains to reveal markers of virulence.
Keywords: Dengue RT-PCR; Plasma; Whole Blood